Vitamin D status in psychotic disorder patients and healthy controls – The influence of ethnic background. Issue 2 (15th December 2015) - Nerhus, Mari; Berg, Akiah Ottesen; Dahl, Sandra Rinne; Holvik, Kristin; Gardsjord, Erlend Strand; Weibell, Melissa Authen; Bjella, Thomas Doug; Andreassen, Ole A.; Melle, Ingrid
Abstract: Vitamin D deficiency is common among patients with psychotic disorders and could be due to unknown disease mechanisms or contingent factors. However most studies are performed in chronic patients and have often failed to address the influence of ethnicity on vitamin D levels in clinical samples. We investigated serum concentrations of 25-hydroxy vitamin D (S-25 OH D) in first episode patients compared to patients with multi episodes and healthy controls; with a specific focus on differences between visible ethnic minorities and participants from the majority population. A total of 284 participants were included in this cross-sectional study. First episode patients with a DSM-IV psychotic disorder were matched on age, gender and ethnicity to participants from a multi episode patient sample (1:1) and healthy controls (1:2). We did not find any differences between either patient groups or the healthy controls, but participants from visible ethnic minorities had significantly lower S-25 OH D than participants from the majority population. This implies that S-25 OH D should be routinely measured in persons from visible ethnic minorities since low levels are associated with higher levels of depressive symptoms. Highlights: Low vitamin D levels in ethnic minorities both in psychotic disorder and in controls. A diagnosis within a psychosis spectrum does not increase the risk of low vitamin D. Low vitamin D is associated with depressive symptoms in first episode patients.